Implementation of Health Protocols in Efforts to Prevent Covid-19 at Islamic Boarding Schools Tambaksari Al Kamal Modern Kebumen Kuwarasan - Agus Istikmal; M Marsito; E Ernawati (Prosiding University Research Colloquium, 2022)
The prevalence of COVID-19 cases in Kebumen Regency reached 4,247 points, with details of 3,463 people recovering and 141 people dying. Confirmed cases of covid- 19 in Kebumen Regency also occurred in Islamic boarding schools. It can be called a new cluster of COVID-19 due to the lack of adherence of students to health protocols. Purposes: To find out the application of health protocols to prevent covid-19 at Al Kamal Islamic Boarding School Tambaksari Kuwarasan Kebumen. Methods: This study used a quantitative descriptive research design with a crosssectional approach. The population of this research was all students of Al Kamal Islamic Boarding School Tambaksari Kuwarasan, 155 respondents joined in this study, and they were chosen by random sampling technique. Data analysis was done by univariate analysis. Result: Most of the students' knowledge about COVID-19 was good category (52.9%), the behaviour of students to wear the masks was good category (49.0%), the behaviour of students to wash their hands was good category (44.5%), and of 63% students did not conduct the social distancing more than one meters. Conclusion: The health protocols as COVID-19 prevention in Al Kamal Islamic Boarding School Tambaksari Kuwarasan had been conducted where students' knowledge and wearing the mask in the good category while the social distancing more than one meter was in the poor category.